Modeling Platform Ecosystems - Pauli, Tobias; Marx, Emanuel; Dunzer, Sebastian; Matzner, Martin (ER Forum, Demo and Posters co-located with 39th International Conference on Conceptual Modeling (ER), 2020)
Platforms facilitate the creation of complementary modulesby third parties and act as intermediaries between different groups of ac-tors. Due to the high degree of collaboration between actors, ecosystemsevolve around such platforms. As a result of digitalization, platform busi-ness models are becoming viable in more and more domains. Despite theincreasing variety of different platform ecosystems, means to clearly spec-ify them are scarce. This conceptual ambiguity impedes comparabilityof research and knowledge accumulation. To solve this problem, we pro-pose a domain-specific platform ecosystems modeling language (PEML)which builds on seminal platform ecosystem literature. We demonstratePEML by modeling two real-life platform ecosystems based on onlinecase studies. Our results support researchers and practitioners alike inclearly specifying platform ecosystem
Keywords: Platform·Ecosystem·Domain-Specific Modeling Language